Antiparasite treatments reduce humoral immunity and impact oxidative status in raptor nestlings - Hanssen, Sveinn Are; Bustnes, Jan Ove; Schnug, Lisbeth; Eulaers, Igor; Jaspers, Veerle; Covaci, Adrian; Eens, Marcel (Ecology and Evolution, 2013)
Abstract: Parasites are natural stressors that may have multiple negative effects on their host as they usurp energy and nutrients and may lead to costly immune responses that may cause oxidative stress. At early stages, animals may be more sensitive to infectious organisms because of their rapid growth and partly immature immune system. The objective of this study was to explore effects of parasites by treating chicks of two raptor species (northern goshawk Accipiter gentilis and white-tailed sea eagle Haliaeetus albicilla) against both endoparasites (internal parasites) and ectoparasites (external parasites). Nests were either treated against ectoparasites by spraying with pyrethrin or left unsprayed as control nests. Within each nest, chicks were randomly orally treated with either an antihelminthic medication (fenbendazole) or sterile water as control treatment. We investigated treatment effects on plasma (1) total antioxidant capacity TAC (an index of nonenzymatic circulating antioxidant defenses), (2) total oxidant status TOS (a measure of plasmatic oxidants), and (3) immunoglobulin levels (a measure of humoral immune function). Treatment against ectoparasites led to a reduction in circulating immunoglobulin plasma levels in male chicks. TOS was higher when not receiving any parasite reduction treatment and when receiving both endo- and ectoparasitic reduction treatment compared with receiving only one treatment. TAC was higher in all treatment groups, when compared to controls. Despite the relatively low sample size, this experimental study suggests complex but similar relationships between treatment groups and oxidative status and immunoglobulin levels in two raptor species.